2013
DOI: 10.14706/jecoss11313
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Capacity Building for Community-Based Small Nonprofit Organizations

Abstract: This article focuses on the inter-organizational networks and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Inter-organizational collaboration strategy (ICS) refers to the relationship of collaboration strategic capacity of education institution, schools, and education formal agency formally to address some problems in basic education to achieve the objectives. The variable has involved at least five indicators, such as connectedness of each actor or stakeholders in the collaboration of basic education, coordination, mutual trust, sharing communication, and innovation alliance (Geisler, 1995;Kapucu & Demiroz, 2013;Oliver & Ebers, 1998;Ritter & Gemünden, 2003). Based on the result findings we argue that the strategic collaboration approach is a pivotal perspective to improve the ENS and service quality in basic education in Indonesia.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Inter-organizational collaboration strategy (ICS) refers to the relationship of collaboration strategic capacity of education institution, schools, and education formal agency formally to address some problems in basic education to achieve the objectives. The variable has involved at least five indicators, such as connectedness of each actor or stakeholders in the collaboration of basic education, coordination, mutual trust, sharing communication, and innovation alliance (Geisler, 1995;Kapucu & Demiroz, 2013;Oliver & Ebers, 1998;Ritter & Gemünden, 2003). Based on the result findings we argue that the strategic collaboration approach is a pivotal perspective to improve the ENS and service quality in basic education in Indonesia.…”
Section: Discussionmentioning
confidence: 89%
“…Based on the literature review, we identify that there are six dimensions of strategic collaboration factors that can determine the success of basic education management and the education standard in the local government and the schooling unit. These dimensions can facilitate the education institution as a public organization to get the best of Service Quality such as; (1) organizational learning and the multiples competencies of actors (Kapucu & Demiroz, 2013;Kim & Park, 2020;Popova-Nowak & Cseh, 2015;Saadat & Saadat, 2016); (2) inter-organizational collaboration capacity (Geisler, 1995;Kapucu & Demiroz, 2013;Oliver & Ebers, 1998;Ritter & Gemünden, 2003); (3) intervention strategies (Cusack et al, 2018;Kapucu et al, 2003;Kapucu & Demiroz, 2013); (4) collaborative capacity networks (Fitzgerald, 2004;Kapucu et al, 2003;Kapucu & Demiroz, 2013); (5) Community Capacity Participation (An et al, 2014;Hite & De Grauwe, 2009;Stoll, 2009). (6) Administrative Management Capacity (Barrera-Osorio et al, 2009;Fullan & Watson, 2000;Kodratillah et al, 2019;Komariah & Sunaengsih, 2016;Wohlstetter & Odden, 2016).…”
Section: Strategic Collaboration Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study by Williams-Gray (2016) suggested that nonprofits that go through a process of evaluating their individual capacity are more likely to build capacity in the future. Finally, Kapucu and Demiroz (2013) found evidence that an organization's capacity can be increased through the use of strong relationships and networks with other nonprofits. Given these findings and the overt focus on a values-framed engagement environment, we investigated the following research question: how does a values-framed engagement environment affect perceptions of organizational capacity?…”
Section: Introductionmentioning
confidence: 99%